The Influence of Education Level, Job Placement, and Job Satisfaction on Employee Performance - Pujiati, Herni; Cahaya, Yohanes Ferry; Yanthy Yosepha, Sri; Anggreani , Noeorlina; Nurmaliza, Nurmaliza (STIE Tri Bhakti, 2025)
This study aims to analyze the influence of education level and job placement on employee performance, with job satisfaction as a mediating variable. The background of this research lies in the importance of human resource management in enhancing employee productivity, particularly in the maritime service sector. A quantitative approach with a survey method was employed. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS 4.0.9.9. The results show that both education level and job placement have a positive and significant impact on employee performance, both directly and indirectly through job satisfaction. Job satisfaction was proven to mediate the relationship between the independent variables and performance, strengthening the positive effects. Appropriate job placement and sufficient education level can improve job satisfaction, which in turn enhances performance. The conclusion of this study suggests that company management should consider aligning education and job placement with individual competencies while also fostering a work environment that promotes job satisfaction. Therefore, proper human resource management strategies can significantly contribute to achieving optimal organizational performance.